TESTING THE VALIDITY OF THE FELDSTEIN-HORIOKA HYPOTHESIS IN DEVELOPED AND LESS DEVELOPED COUNTRIES BY PANEL DATA ANALYSIS (Third Sector Social Economic Review, 2024)
In this study, prepared within the scope of the Feldstein-Horioka hypothesis, which tries to analyze the relationship between savings and investments by adhering to the degree of liberalisation of international capital movements; horizontal cross-section dependence, delta homogeneity, panel unit root and cointegration tests and finally Emirmahmutoğlu and Köse (2011) causality test are applied with the help of annual data on the ratios of investment and savings to gross domestic product covering the period 2000-2021 for 37 developed and less developed  countries. As a result of the findings, it was concluded that the Feldstein–Horioka hypothesis is valid. Accordingly, it has been determined that there is a long-term relationship between savings and investments; it has been seen that a shock in any country will affect other countries as well.
Keywords: Feldstein-Horioka; Panel data analysis; Capital Mobility; Saving; Investment